An unprecedented zero field neodymium(iii) single-ion magnet based on a phosphonic diamide. Issue 44 (13th May 2016) - Gupta, Sandeep K.; Rajeshkumar, Thayalan; Rajaraman, Gopalan; Murugavel, Ramaswamy
Abstract : A pseudo- D 5h symmetric Nd(iii )-complex exhibits zero-field SIM behavior as a result of a strong axial crystal field, stabilization of the rare m J = |±9/2〉 ground state, and small transverse anisotropy. Abstract : The axial ligation by the –PO group of a phosphonic diamide in an air-stable Nd(iii ) complex ensures a pseudo- D 5h symmetry leading to the stabilization of the m J = |±9/2〉 state; this in turn is responsible for the observed SIM behaviour at zero field and the slow relaxation of magnetization up to 8.0 K.